FORUM MŁODYCH CHIRURGÓWIntraoperative use of transoesophageal echocardiography in routine mitral valve replacement – a justified standard - Olszówka, Piotr; Azzu, Ahmed; Karthikeyan, Sivagnanam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The role of intraoperative transoesophageal echocardiography (TEE) in valve replacement surgery is still not well established. The aim of presenting this case was to justify the standard use of TEE in routine valve replacement surgery. A patient admitted for elective mitral valve replacement with coronary artery bypass grafting with known moderate aortic stenosis underwent surgery. The mitral valve was replaced with a St. Jude mechanical valve. The aortic valve was decalcified and a single coronary bypass graft was done. Bypass TEE revealed a short period when one leaflet of the prosthetic valve was stuck. The patient was weaned easily from cardiopulmonary bypass without inotropic support. Postoperative TEE in the theatre revealed both well mobile leaflets with an extra echo shadow above the valve in the left atrium. Re-exploration confirmed the presence of residual tissue across the valve. The intraoperative use of TEE plays an important diagnostic and therapeutic role in valve replacement surgery and should be widely implemented.